2011
DOI: 10.1016/j.devcel.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E Constrains Cdk5 Activity to Regulate Synaptic Plasticity and Memory Formation

Abstract: SUMMARY Cyclin E is a component of the core cell cycle machinery, and it drives cell proliferation by regulating entry and progression of cells through the DNA synthesis phase. Cyclin E expression is normally restricted to proliferating cells. However, high levels of cyclin E are expressed in the adult brain. The function of cyclin E in quiescent, postmitotic nervous system remains unknown. Here we use a combination of in vivo quantitative proteomics and analyses of cyclin E knockout mice to demonstrate that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 50 publications
(68 reference statements)
5
109
0
1
Order By: Relevance
“…The Cdk2-cyclin E complex is critical for G1/S transition of the cell cycle and DNA synthesis (Tsai et al, 1993). Recent studies have shown that cyclin E is also highly expressed in adult brain where it forms a complex with Cdk5 (Odajima et al, 2011). Interestingly, instead of activating Cdk5, the binding of cyclin E inactivates Cdk5 and sequesters it away from its normal activators p35 and p39 (Odajima et al, 2011).…”
Section: Cyclin Ementioning
confidence: 99%
See 1 more Smart Citation
“…The Cdk2-cyclin E complex is critical for G1/S transition of the cell cycle and DNA synthesis (Tsai et al, 1993). Recent studies have shown that cyclin E is also highly expressed in adult brain where it forms a complex with Cdk5 (Odajima et al, 2011). Interestingly, instead of activating Cdk5, the binding of cyclin E inactivates Cdk5 and sequesters it away from its normal activators p35 and p39 (Odajima et al, 2011).…”
Section: Cyclin Ementioning
confidence: 99%
“…Recent studies have shown that cyclin E is also highly expressed in adult brain where it forms a complex with Cdk5 (Odajima et al, 2011). Interestingly, instead of activating Cdk5, the binding of cyclin E inactivates Cdk5 and sequesters it away from its normal activators p35 and p39 (Odajima et al, 2011). Moreover, cyclin-E-mediated sequestering of Cdk5 promotes dendritic growth, synaptic plasticity and memory formation in transgenic animal models, suggesting that cyclin-Emediated inhibition of Cdk5 is physiologically relevant (Fig.…”
Section: Cyclin Ementioning
confidence: 99%
“…For example, Drosophila E2F is required for transfer of cytoplasm from nurse cells to oocytes, and for the establishment of oocyte dorsal-ventral polarity (Myster et al, 2000). In postmitotic mammalian neurons, constitutively expressed CycE binds to and inhibits Cdk5 to control synaptic plasticity and memory formation (Odajima et al, 2011). Activation of Cdk5 in adipocytes as a result of high fat-induced obesity also leads to PPAR phosphorylation and deregulated expression of insulin-sensitizing genes independently of cyclins (Choi et al, 2010).…”
Section: F36mentioning
confidence: 99%
“…We have recently described that Cdk5 physically interacts with and phosphorylates SynIII at a unique phosphorylation site (Ser 404 ) that is crucial for the regulation of radial migration of pyramidal neurons in the developing neocortex (Perlini et al, 2015). SynIII and Cdk5 are coexpressed at perinatal ages in the cortex, but thereafter their expression patterns diverge (Ferreira et al, 2000;Odajima et al, 2011;Perlini et al, 2015). Before addressing the role of Cdk5 phosphorylation of SynIII, we checked the distribution of SynIII and p35, the neurospecific Cdk5 activator, in WT cortical neurons at 3 and 14 DIV.…”
Section: A Novel Cdk5 Phosphorylation Site On Syniii Regulates Its Fumentioning
confidence: 99%